STUDY OF DRABBLES IN WORLD LITERATURE (Scientific journal of the Fergana State University, 2024)
This article talks about the stages of development of the drabble genre in world literature, in particular in English literature, their features and role in today's modern literature, in particular in English literature. Also, despite the fact that drabble is a new genre, many contemporary writers in this field and their works are analyzed. In addition, the works of famous English writers (stories, stories, drabbles) and their genre characteristics, the realities in the drabbles they created, selected expressions and, of course, drabbles created by order are analyzed.